Human immunodeficiency virus infection - treatment beyond medication. - Teixeira, Carla (2010)
Human Immunodeficiency Virus (HIV) infection is presently considered a chronic disorder. Infected people need a thorough medical surveillance and chronic therapy, which affects families and other caregivers. Infected children are also affected by their parents' infection and by the stigma that is still associated with this particular illness. Regular meetings were organized for HIV infected children, their families and the health team with recreational and formative purposes. These meetings were evaluated in a strongly positive manner by all the intervenients. The goal to maintain these activities is proposed as a way of improving the follow-up and the prognosis of these children.